PANDEMI COVID-19 SEBAGAI ALASAN PERUSAHAAN UNTUK MELAKUKAN PEMUTUSAN HUBUNGAN KERJA (PHK) SECARA SEPIHAK - Siti Frivanty (©2021 UM- Tapsel Press, 2021)
Law Number 13 of 2003 concerning Manpower does not allow companies to terminate employees who comply with the obligations stipulated in the work agreement. But, during the Covid-19 pandemic, in Depok, there were 397 workers who were laid off, and 1,282 workers had to be suspended. The research discusses the companies' reasons for the layoffs during the pandemic and forms of legal protection for workers who are laid off because of the Covid-19 pandemic. This qualitative study uses a normative juridical approach using secondary data. Based on the analysis' results, 2 things were found, first, the layoffs during the Covid-19 pandemic was a force majeure, which resulted in a decrease in sales turnover to the closure of the company; second, the form of protecting companies that did unilateral layoffs because of the pandemic is to provide compensation to their workers.